Removal of Methylene Blue from Aqueous Solution Using Agricultural Residue Walnut Shell: Equilibrium, Kinetic, and Thermodynamic Studies - Ranxiao Tang; Chong Dai; Chao Li; Weihua Liu; Shutao Gao; Chun Wang (Journal of Chemistry)
Walnut shell (WS), as an economic and environmental-friendly adsorbent, was utilized to remove methylene blue (MB) from aqueous solutions. The effects of WS particle size, solution pH, adsorbent dosage and contact time, and concentration of NaCl on MB removal were systematically investigated. Under the optimized conditions (i.e., contact time ~ 2 h, pH ~ 6, particle size ~ 80 mesh, dye concentration 20 mg/L, and 1.25 g/L adsorbent), the removal percentages can achieve ~97.1%, indicating WS was a promising absorbent to remove MB. Other supplementary experiments, such as Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), and Brunauer-Emmett-Teller (BET) method, were also employed to understand the adsorption mechanisms. FTIR confirmed that the successful adsorption of MB on WS particles was through functional groups of WS. Using DLS method, the interactions between WS particles and dyes under various pH were investigated, which can be ascribed to the electrostatic forces. Kinetic data can be well fitted by the pseudo-second-order model, indicating a chemical adsorption. The adsorption isotherms were well described by both Langmuir and Freundlich models. Dubinin-Radushkevich model also showed that the adsorption process was a chemical adsorption. Thermodynamic data indicated that the adsorption was spontaneous, exothermic, and favorable at room temperature.